Incidence of early adverse events following covishield (ChAdOx1 nCoV-19) vaccination: A prospective study - Gajanan D Velhal; Yash V Kamath; Ansh S Agrawal; Devanshi S Vora; Vaibhav R Dwivedi (Wolters Kluwer Medknow Publications, 2022)
Background: Minor adverse event following immunizations (AEFIs) are often underreported and self-treated. This study aimed to collect information regarding any and every probable adverse event experienced by the recipient of Covishield vaccine up to 10 days following the first and second dose of vaccine. To find the incidence of minor adverse events following Covishield vaccination; draw an association between adverse events and individuals' demographic factors and comorbidities; and report new adverse events, if any. Materials and Methods: A descriptive observational study was conducted among 409 participants randomly sampled from the Vaccination Centre at a Tertiary Care Hospital, Mumbai. Participants were followed up post their first and second doses to enquire about adverse events. Results: Most commonly reported adverse events included injection site pain, tenderness, chills, fatigue, fever, and myalgia. Females reported more adverse events compared to men (p < 0.05). Younger individuals (18-24) experienced adverse events more as compared to individuals above 40 years of age (p < 0.005). Reported adverse events were lesser after the second dose in comparison with the first dose. Few participants reported dysgeusia. Conclusions: Covishield vaccination has a mild AEFI profile, most commonly: injection site pain, tenderness, chills, and fatigue. It is hoped that the findings of this study will dispel anxiety around the adverse events of vaccination and reduce any persisting vaccine hesitancy. Effective communication with the population on vaccination will enable individuals to make educated and informed decisions.